PRIMBON JAWA MADURA: Salep Tarjeh Dan Weton Desa Bulupitu - Ulum, Bahrul (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2022)
This research is aimed at studying the Primbon culture of the residents of Bulupitu Village in its application in marriage practices to find out and compare the impact of Primbon on the sustainability of marriages that apply this system and marriages that do not apply the Primbon system and the perspective of Islamic law in addressing this practice. This research is in search of data with field studies using a qualitative approach with data collection methods, namely; Interviews, Literacy Studies, and Observations From this study it was found that in the application of Primbon, Bulupitu Village residents were divided into two camps, namely those who applied the Primbon system in their marriage (Kejawen) and those who did not apply it (Potehan). The Kejawen adhere to the Primbon concept starting from Weton, Salep Tarjeh, and Wedding Day, while the Potehan refuse to believe in this. Nevertheless, these taboos and recommendations still have an effect on the sustainability of the marriage mahligai of Bulupitu residents if they are violated or carried out. Primbon culture actually does not conflict with the concept of Islamic law because it is a custom that has its own legal basis, namely 'Urf and is a form of endeavor and